The importance of animal studies in Exercise Science - Angelis, Kátia De; Rodrigues, Bruno; Zanesco, Angelina [UNESP]; Oliveira, Edilamar Menezes De; Evangelista, Fabiana De Santa`anna; Coelho, Helio Jose; Andreia Delbin, Maria; Chakur Brum, Patricia; Ramires, Paulo Rizzo; Soares, Pedro Paulo; Wichi, Rogério Brandão; Amaral, Sandra Liado [UNESP]; et al. (Universidade Estadual Paulista, 2017)
The validity and relevance of research with animals for the development of knowledge in Exercise Science have for long been discussed. Given the complexity of the biological systems, the use of animal models offers a significant contribution to uncover new findings about acute and chronic effects of exercise, particularly when these studies in humans have limitations and ethical implications. There have been notable findings using experimental animals either in basic sciences or in clinical studies involving physiology, pharmacology, genetic, biochemistry, urology, endocrinology and cancer. This article presents a brief review of scientific research using animal models with a focus on exercise training as an effective tool for the prophylaxis and treatment of different pathological processes, which are the basis of many concepts taught and used in undergraduate courses and graduate programs, as well as in new researches showed in scientific conference meetings in numerous areas of science.
Keywords: animal studies; exercise science; physical education; sport; knowledge evolution.